Chlorantraniliprole induces adipogenesis in 3T3-L1 adipocytes via the AMPKα pathway but not the ER stress pathway. (1st May 2020) - Yuan, Li; Lin, Jie; Peng, Ye; Gao, Ruichang; Sun, Quancai
Highlights: Chlorantraniliprole promotes adipogenesis in 3T3-L1 adipocytes. Chlorantraniliprole inhibits the activation of AMPKα. Chlorantraniliprole has no influence on ER stress. Abstract: Flubendiamide, a ryanoid family insecticide, has been linked to elevated adipogenesis. However, the influence on adipogenesis of chlorantraniliprole, another widely-used ryanoid-class insecticide in agriculture, remains unknown. Therefore, the influence of chlorantraniliprole on adipogenesis was studied in 3T3-L1 cells. Chlorantraniliprole enhanced TG content and upregulated the expression of C/EBPα, PPARγ, and ACC, three key adipogenic regulators. Chlorantraniliprole decreased the phosphorylation of AMPK, while it had no influence on the expression of endoplasmic reticulum stress regulators. The influence of chlorantraniliprole on adipogenesis was abolished by AMPKα activation. Collectively, the results indicate that chlorantraniliprole enhances adipogenesis through the AMPKα pathway, but not the ER stress-mediated pathway.